Strategi Pengembangan Perusahaan Agroindustri (Studi Kasus PT Citra Rahardja Utama di Kecamatan Gamping Kabupaten Sleman) - Indah Widowati (Universitas Muhammadiyah Yogyakarta, 2015)
This study aimed to analyze the appropriate strategy for PT Citra Utama Rahardja in maintaining business continuity. The case study method was used in this research, as PT Rahardja Citra Utama was a company that processes albasia wood (sengon) into barecore in Yogyakarta. The sources of data was taken from primary and secondary data. The results showed from SWOT analysis diagram was that layout of the company was in quadrant I, that was supported an aggressive strategy which included the integration of backward, forward, horizontal; market penetration; market development; product development; diversification (related or unrelated). Based on the calculation of SPACE matrix (Matrix of Strategic Position and Action Evaluation) the coordinate of SPACE matrix diagram on the X-axis was 1,785 and Y-axis was 0,16 that was in quadrant I. The competition ability of PT Citra Utama Rahardja was considered as high and able to respond the variable of external factors.